2013
DOI: 10.1093/infdis/jit009
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Chlamydia-Induced Infertility by Inhibition of Local Caspase Activity

Abstract: Tubal factor infertility (TFI) represents 36% of female infertility and genital infection by Chlamydia trachomatis (C. trachomatis) is a major cause. Although TFI is associated with host inflammatory responses to bacterial components, the molecular pathogenesis of Chlamydia-induced infertility remains poorly understood. We investigated the hypothesis that activation of specific cysteine proteases, the caspases, during C. trachomatis genital infection causes the disruption of key fertility-promoting molecules r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
65
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 48 publications
9
65
0
1
Order By: Relevance
“…Thus, when infected Z-VAD-FMK treated and non-treated mice were monitored for chlamydial shedding, Figure 1 shows that all animals were infected to the same degree and shed chlamydiae from their genital tracts to the same intensity during the initial 2 weeks covering the peak period of shedding after infection. However, as shown in Figure 2, treatment with the pan-caspase inhibitor, Z-VAD-FMK protected infected mice from infertility, as previously reported [19]. To identify the specific initiator caspase that mediate infertility, groups of mice were treated with specific inhibitors of the key initiator capases (caspase-1, -3 and -8), namely Z-WEHD-FMK, Z-DEVD-FMK, and Z-IETD-FMK, respectively, and fertility was assessed after infection.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Thus, when infected Z-VAD-FMK treated and non-treated mice were monitored for chlamydial shedding, Figure 1 shows that all animals were infected to the same degree and shed chlamydiae from their genital tracts to the same intensity during the initial 2 weeks covering the peak period of shedding after infection. However, as shown in Figure 2, treatment with the pan-caspase inhibitor, Z-VAD-FMK protected infected mice from infertility, as previously reported [19]. To identify the specific initiator caspase that mediate infertility, groups of mice were treated with specific inhibitors of the key initiator capases (caspase-1, -3 and -8), namely Z-WEHD-FMK, Z-DEVD-FMK, and Z-IETD-FMK, respectively, and fertility was assessed after infection.…”
Section: Resultssupporting
confidence: 85%
“…To better characterize the contributions of the host and pathogen to chlamydial disease, we recently reported that although both the wild-type and the plasmid-free strain of C. trachomatis could colonize the genital tracts of female mice, the latter failed to induce infertility as compared to the former [19]. In addition, the local genital tract application of the pan-caspase inhibitor, Z-VAD-FMK conferred protection against infertility without affecting infectivity, as assessed by shedding of chlamydiae into the cervic-vaginal vault [19].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations